What is Required for Advancing REDD+? (Progress to Date and Challenges Ahead) - Mitsuo Matsumoto (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
To facilitate international discussion and research on the REDD+ framework and associated programs, I present an overview of the historical background, major rules, and challenges of implementing REDD+. The framework of REDD+ is illustrated using examples from scientific literature and the agreements adopted by the United Nations Framework Convention on Climate Change (UNFCCC). The institutional challenges related to REDD+ are discussed in the context of how to promote and implement REDD+ activities. Key issues for advancing REDD+ in the future include the establishment of a financial framework, the transferability of results, the risk of double counting, the timing of payments, and the domestic distribution of funds. Because agreements related to REDD+ do not mention transfers or trade of results from REDD+ activities, the transfer of results might give disincentives to developing countries; thus, allowing transfers or trade may actually limit REDD+ activities. Therefore, it seems preferable that the results of reduced emissions and increased removals through REDD+ activities, through publicly financed programs under the UNFCCC and Green Climate Fund (GCF), should be non-transferable. The transferability of results through REDD+ activities is important to consider, especially for different schemes such as the Forest Carbon Partnership Facility (FCPF) and the Joint Crediting Mechanism (JCM), because double counting can occur between countries and between schemes. Although I support advance performance-based payments for the planning and implementation of REDD+ activities, which is a similar concept to that discussed by the GCF, appropriate indicators and transparent methods for monitoring and evaluating performance will be required.